Analisis Implikasi Pembiayaan Syariah pada Pedagang Kecil di Pasar Tanjung Jember - Choirin Nikmah; Hari Sukarno; Ana Mufida (e-Journal Ekonomi Bisnis dan Akuntansi, 2014)
This research is a descriptive study aims to describe the implications of Islamic finance is the financing type of Mudharaba and Musharaka financing types based on the financial performance of Merchants. Measurement of financial performance views of assets, sales turnover and profits earned or owned by Merchants in the vulnerable period of 4 weeks . Sampling techniques such as random sampling with a total of 26 samples of Merchants . The analytical method used is the method of graphs and tables . The results of this study illustrate that small traders who have got the type of Islamic finance in the form of Mudharaba and Musharaka financing of BMT Bina Tanjung average to increase assets , sales turnover and profit well . This can be seen from the table and graph growth that Merchants who got the manifold mudharaba and Musharaka financing has increased assets , sales turnover and profits from the first week to the fourth week .